Biocrusts Influence Vascular Plant Community Development, Promoting Native Plant Dominance - Bowker, Matthew A.; Doherty, Kyle D.; Antoninka, Anita J.; Ramsey, Philip W.; DuPre, Mary Ellyn; Durham, Rebecca A. (Frontiers in Ecology and Evolution, 2022)
The soil and its biota can shape the development of colonizing vascular plant communities. Because they occupy soil surfaces where most seeds disperse to, biological soil crusts (biocrusts) are uniquely positioned to influence vascular plant communities established by direct seeding, e.g., for restoration. We created mesocosms of soil overtopped by intact biocrust transplants from the field, varying in key community attributes: total cover, species richness, and proportional cover of mosses relative to lichens. We seeded the same diverse mixture of vascular plants into all mesocosms, including desired native species and problematic exotic invasive species. We tracked plant community development for two full growing seasons, both under ambient outdoor conditions and with supplemental irrigation to remove the influence of water limitation. Under ambient conditions, we found that total biocrust cover suppressed exotic plant emergence and biocrust richness slightly promoted native emergence (r = -0.23 to -0.39) but had weaker and less consistent effects on cover of either native or exotic plants (r ≤│0.25│). Early emergence events were generally strong drivers of vascular plant recruitment (r = 0.17 to 0.78) and continued to influence community composition after two years, suggesting a priority effect. Biocrust cover also promoted final plant biomass under ambient conditions (r = 0.17 to 0.33) but did not influence the total cumulative number of native species (r ≤ │0.07│) nor the fecundity of exotics (r ≤ │0.08│). Biocrusts’ influence on total vascular plant biomass was minor. When water was added, biocrust effects sometimes switched from positive or negative to neutral, or vice-versa, indicating that our detection probability of biocrust effects on plants changes with moisture availability. Our results demonstrate that the condition of pre-existing biocrust communities can influence—but not strongly dictate—the outcome of multi-species restoration seedings, mostly positively or neutrally under normal conditions, but switching to potentially negatively under irrigated conditions. Our study also suggests that locations with more intact and richer biocrust communities might be slightly more conducive to successful seeding outcomes, while also providing additional contributions to ecosystem functions. As such, biocrusts, alongside vascular plants, have a role in restoring damaged or degraded ecosystems.